Study of Complexation Behaviour of Lignite Extracted Humic Acid with Some Divalent Cations - Iqbal, Pervez; Aftab , Kiran (Engineering Science Letter, 2023)
In biogeochemical cycles, humic substances are natural electron shuttles in transforming nutrients and environmental pollutants. Humic acid complexes with macro and micronutrient metals are eco-friendly organo-mineral fertilisers. This study prepared and characterised lignite-extracted humic acid-metal (Fe, Mg, Zn) complexes. The proximate analysis exhibited the moisture, volatile matter, ash and fixed carbon contents of extracted humic acid of 02.61%, 17.31%, 57.18% and 22.90%, respectively. The percentage of metal ions in humic acid complexes ranges from 3.5-7.25%. The FTIR analysis of coal-extracted humic acids-metal complexes showed Zn, Mg and Fe ions complexed in a bidentate manner predominantly with the carboxylic acid moiety of humic acid. Thermal gravimetric analysis indicated a higher value of humic acid decomposition than their metal complexes. The thermal stability observed order is HA- Zn >HA-Fe>HA- Mg. The X-ray diffraction pattern pointed toward the noncrystalline nature of humic acid and their respective complexes due to having few intense and small diffuse peaks in the 2θ range from 0 to 80°. Hence, the humic acid-metals complexes increase the soil humic content and the availability of essential nutrients that enhance the loam's biotic action.